2000
DOI: 10.1021/jp994269k
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone-Analogue Dyes Emitting in the Near-Infrared (NIR):  Influence of Donor−Acceptor Substitution and Cation Complexation on Their Spectroscopic Properties and X-ray Structure

Abstract: The photophysical properties of several newly synthesized 1-benzothiazole-3-(4-donor)-phenyl-substituted prop-2-en-1-ones (substituted chalcones) are studied as a function of solvent polarity, temperature, and metal ion by employing steady-state and time-resolved spectroscopy. To investigate the effect of bulkiness and donor strength of the anilino moiety on the spectroscopic properties of these dyes, the spectroscopic behavior of the 4-N-dimethylamino (DMA), the 4-N-tetraoxa-monoaza-15-crown-5 (A15C5), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 122 publications
8
99
0
Order By: Relevance
“…In spite of it there are versatile chemical and physical properties, and there are very limited data describing the photochemical and physical properties of these compounds. Recent reports related cocoons are widely used for various optical applications including second harmonic generation materials in nonlinear optics, photorefractive polymers, holographic recording materials and fluorescent probes for sensing of metal ions [9][10][11][12][13][14][15][16][17][18]. How- * corresponding author; e-mail: aminosman81@gmail.com ever, the photophysical properties of these chalcones such as solvent environment, temperature effect and quantum yield of fluorescence were not fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of it there are versatile chemical and physical properties, and there are very limited data describing the photochemical and physical properties of these compounds. Recent reports related cocoons are widely used for various optical applications including second harmonic generation materials in nonlinear optics, photorefractive polymers, holographic recording materials and fluorescent probes for sensing of metal ions [9][10][11][12][13][14][15][16][17][18]. How- * corresponding author; e-mail: aminosman81@gmail.com ever, the photophysical properties of these chalcones such as solvent environment, temperature effect and quantum yield of fluorescence were not fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have also been reported by Fayed for other types of fluorescent solvatochromic dyes [23], and can be explained by several mechanisms such as biradicaloid charge transfer, proximity effect and conformational changes. The dramatical decrease of the quantum yield in the protic polar alcohols is assumed to be due to hydrogen bonding interactions between the dye and the solvent, giving rise to enhanced non-radiative losses and quenching [19,24,25]. The existence of specific dye-solvent interactions in protic solvents is also supported by the particular spectral behavior of KSD-4 in alcohols, as mentioned above (Fig.…”
Section: Spectral Properties Of Ksd-4 and Ksd-4cmentioning
confidence: 82%
“…Copyright 2005 American Chemical Society responsible for the solvatochromic properties of these dyes in aprotic solvents, specific interaction involving formation of intermolecular hydrogen-bond provides stronger solvatochromic behavior of these dyes in protic solvents. Workers from different groups have also shown that the ketocyanine dyes form strong hydrogenbonded complexes both in the ground state and in the excited state [113][114][115][116]. However, the fluorescence efficiency of these dyes is seen to be reduced significantly in protic solvents due to hydrogen-bonding interaction with the solvent.…”
Section: Ketocyanine Dyes-alcohol Systems (Refs [111112])mentioning
confidence: 99%